1992
DOI: 10.1111/j.1365-246x.1992.tb00845.x
|View full text |Cite
|
Sign up to set email alerts
|

King's Trough: reactivated pseudo-fault of a propagating rift

Abstract: A compilation of magnetic data in the western North Atlantic shows that seafloor spreading magnetic anomalies 26 to 18 are dislocated across a (pseudo-) fault with a direction mirroring that of King's Trough. It is interpreted that this feature and King's Trough were formed by northward propagation of the rift, initiated by a hotspot that created the Azores-Biscay Rise. The rift propagation stopped when King's Trough became part of the plate boundary between Eurasia and Iberia at chron 17. Most of the present-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The resulting north pointing V‐shaped feature (Figures 8 and 13) comprises the third pair of legs. Kings Trough was once the plate boundary between Eurasia and Iberia [ Srivastava et al , 1990] and is suggested to have formed as a shear zone by the northward propagation of the spreading rift, with the conjugate high on the western flank being the trace of the mirrored pseudofault [ Srivastava and Roest , 1992]. As such, these legs have no apparent relation to a hot spot, although the thickened crust could have been associated with elevated melt production in fertile mantle rising at the plate boundary.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting north pointing V‐shaped feature (Figures 8 and 13) comprises the third pair of legs. Kings Trough was once the plate boundary between Eurasia and Iberia [ Srivastava et al , 1990] and is suggested to have formed as a shear zone by the northward propagation of the spreading rift, with the conjugate high on the western flank being the trace of the mirrored pseudofault [ Srivastava and Roest , 1992]. As such, these legs have no apparent relation to a hot spot, although the thickened crust could have been associated with elevated melt production in fertile mantle rising at the plate boundary.…”
Section: Discussionmentioning
confidence: 99%
“…Iberia has been studied extensively since the 1980s through models describing the southern North Atlantic kinematics. These models were based on the analysis of marine magnetic anomalies and bathymetric or gravity data (DeMets et al, ; Kerr et al, ; Klitgord & Schouten, ; Merkouriev & DeMets, , , ; Miles & Kidd, ; Müller & Roest, ; Müller et al, , , ; Olivet et al, ; Olivet, ; Roest & Srivastava, ; Srivastava & Tapscott, ; Srivastava & Roest, , , ; Srivastava, Roest, et al, ; Srivastava, Schouten, et al, ; Srivastava et al, ; Sibuet & Collette, ; Sibuet, Srivastava, & Spakman, ; Sibuet, Monti, et al, ; Torsvik et al, ; Verhoef et al, ; Vogt, ) or on the reinterpretation of previously published data sets (e.g., rotation poles) to remove inconsistencies in the kinematic reconstructions (Rosenbaum, Lister, & Duboz, ; Vissers & Meijer, , ). The seafloor spreading history of the southern North Atlantic between Iberia and Newfoundland and its relationship to the formation of the Pyrenees and Betic‐Rif system (Figure ) has been described involving successive jumps of the plate boundary between Iberia, Europe, and Africa from north (Bay of Biscay axis, B and King's Trough, KT; Figure ) to south (Azores Gibraltar Fracture Zone, AGFZ; Figure ) (Klitgord & Schouten, ; Olivet, ; Roest & Srivastava, ; Rosenbaum et al, ; Sibuet, Srivastava, & Spakman, ; Srivastava, Roest, et al, ; Srivastava, Schouten, et al, ; Vissers & Meijer, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Topographic‐bathymetric map of the southern North Atlantic. Red lines: plate boundaries; white lines: fracture zones; AGFZ: Azores Gibraltar FZ; ATJ: Azores Triple Junction; B: Bay of Biscay axis; CGFZ: Charlie Gibbs fracture zone; GB: Guadalquivir Bank; GF: Gloria Fault; GR: Gorringe Ridge; KT: King's Trough; MAR: mid‐Atlantic ridge; PF: pseudo‐fault, according to Srivastava and Roest (). The yellow box shows the location of the study area and where Figures , and are featured.…”
Section: Introductionmentioning
confidence: 99%